Towards A Directors' Competition Disqualification Regime in Nigeria: Lessons from the UK. (5th June 2021) - Subai, Pereowei; Caliskan, Samet
Abstract: This article argues that Nigeria should introduce a competition disqualification regime for company directors as a deliberate strategy to foster corporate compliance with the Federal Competition and Consumer Protection Act 2018. It contends that the custodial and financial sanctions provided for under the act may not sufficiently deter directors from engaging in anti-competitive behaviour. It seeks to demonstrate that the "threat" of incarceration, which would ordinarily have a strong deterrent effect, is rarely imposed, as courts tend to prefer imposing fines on directors and individuals who breach competition law. For that reason, the article proposes that Nigeria should adopt a strategy of disqualifying directors who oversee companies that breach competition law, or who are complicit in that regard, as a means of complementing existing sanctions. In order to achieve its objective, the article examines the competition disqualification regime in the UK in order to extract valuable lessons that Nigeria can emulate.